Impact Analysis of Sustainable Financial Reporting and Environmental Regulatory Compliance on Decision Making Effectiveness in Bandung Manufacturing Industry - Mei Rani Amalia; Tera Lesmana; Rani Eka Arini (Westscience Press, 2024)
This research investigates the impact of sustainable financial reporting and compliance with environmental regulations on decision-making effectiveness within the Bandung manufacturing industry. A quantitative analysis was conducted using survey data collected from manufacturing firms in Bandung, Indonesia. Descriptive statistics, correlation analysis, and multiple regression analysis were employed to examine the relationships between sustainable financial reporting, environmental regulations compliance, and decision-making effectiveness. The results reveal significant positive correlations between sustainable financial reporting, environmental regulations compliance, and decision-making effectiveness. Regression analysis demonstrates that both sustainable financial reporting and environmental regulations compliance are significant predictors of decision-making effectiveness, even after controlling for relevant covariates. These findings underscore the importance of integrating sustainability principles and regulatory compliance into organizational decision-making processes to enhance performance outcomes and stakeholder value within the manufacturing sector.